Relationship between COVID-19 Outbreak with Non-Communicable Disease and Multisystem Inflammatory Syndrome in Children: A Narrative Review - Nabi, Shah Golam; Islam, Saiful; Jahan, Zakia (Bangladesh Journal of Infectious Diseases, 2025)
The coronavirus disease 2019 (COVID-19) outbreak forced us to fight against the unprecedented times in the world. A big devastating impression on the world due to the COVID-19 outbreak causes the brink of no return. The COVID-19 pandemic has significantly influenced various facets of society, including its profound effects on children and the prevalence of non-communicable diseases (NCDs). Quarantine regulations have altered children's and teenagers' typical lifestyle routines. In this study, we address the possible short- and long-term impacts of high-risk NCD behaviors on health outcomes and how the COVID-19 pandemic affected childhood lifestyle. Bangladesh Journal of Infectious Diseases, December 2024;11(2):166-171